Reliability and Validity of Urdu Version of the Dynamic Gait Index in Pakistani Geriatric Population - Waheed, Aqsa; Kashif, Muhammad; Ghaffar, Tamjeed; Khalid , Mahzaib; Afzal, Shama; Asif , Rizwan (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To translate DGI into Urdu and examine its reliability and validity in the Pakistani geriatric population. METHODOLOGY: This cross-sectional study was conducted in Faisalabad from April to September 2021. The English version of DGI was translated into Urdu and culturally adapted. The DGI-U was administered by convenience sampling; a sample size of 56 geriatric patients enrolled based on predefined inclusion criteria. Participants with a minimum age of 65, walking without aids for at least 6 meters, falling at least once in the last year, and subjectively examining balance disorder were included. Patients who could not understand the DGI instructions had lower limb injuries/had undergone knee/hip reconstruction during the past three months were excluded. Test-retest reliability was determined by administering the DGI-U twice, and inter-rater reliability was determined by administering it alone on the same day by two raters. Internal consistency was reported using Cronbach’s alpha. Pearson’s correlation analysis was used to examine the concurrent validity of the Urdu version of the DGI with the TUG and Berg Balance Scale (BBS). RESULTS: Internal consistency (Cronbach’s alpha = 0.97) of the Urdu version of DGI was excellent. DGI-U reflected high inter-rater reliability (ICC=0.959; 95% Cl (0.931-0.976) and intra-rater reliability (ICC=0.952 95% Cl (0.915-0.973). The DGI-U was correlated positive moderate with TUG (r = .716, p .0001) and BBS (r = 0.692, p .0001) CONCLUSION: The study provided adequate evidence for the validity and reliability of the Urdu version of DGI for use in the elderly Pakistani population.